Exercício físico, marcadores inflamatórios e genótipo da APOE em idosos com comprometimento cognitivo leve e idosos cognitivamente preservados - Nascimento, Carla Manuela Crispim [UNESP] (2014)
Low-grade chronic inflammation has been recognized as a significant pathway on neurodegenerative process, mainly on elderly with mild cognitive impairment (MCI). Regular practice of physical exercises has been demonstrated as a feasible alternative to reduce blood concentrations of some cytokines, including in elderly. Thus, physical exercises are a non-pharmacological strategy important to help on the healthy ageing. The main goals of this study were: a) to analyze the effects of 16-weeks of a multimodal physical exercises program on peripheral concentrations of inflammatory markers in elderly with MCI and on cognitive healthy elderly; b) to analyze if the APOE genotype could influence on the effects of this program and; c) to identify if the peripheral concentrations of pro-inflammatory cytokines, APOE genotype and practice of physical exercises could contribute as predictors of MCI on the subjects. Participated on the research 67 elderly, distributed on four subgroups according to the presence of MCI and the participation on the proposed program of multimodal physical exercises during 16-weeks (trained group with MCI: n=20; trained group cognitive healthy: n=15; control group with MCI: n=17; control group cognitive healthy: n=15). All participants were assessed by the Clinical Dementia Rating scale; Instrumental Activities Pfeffer Questionnaire; Geriatric Depression Scale-short form; Montreal Cognitive Assessment; Physical Function Battery of American Alliance for Health, Physical, Education, Recreation and Dance; beyond laboratorial analysis to determine APOE genotype, glucoses levels, triglycerides, HDL and LDL cholesterol and serum concentrations of pro-inflammatory cytokines: Tumor Necrosis Factor-α (TNF-α) and Interleukin-6 (IL-6). The main findings of this research indicated that: a) subjects who took part in a multimodal physical exercises program presented significant reductions on TNF-α and IL-6 peripheral concentrations...